Peningkatan Kompetensi Materi Komunikasi Bisnis Bagi Guru Bisnis Daring dan Pemasaran Jawa Timur - Tri Sudarwanto; Dwi Yuli Rakhmawati; Erta; Hapsari Shinta Citra Puspita Dewi; Putri Hestiningrum; Febrika Yogie Hermanto (Inspirasi: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
This Program aims to improve the competence and abilities of teachers at the Online Business and Marketing Subject Teacher Consultation (MGMP) in Surabaya in the field of business communication. The method of implementing the activities is through training and mentoring. The era of competitive digital transformation makes the demands of the times grow rapidly. Problems that often occur are always related to the communication that will be faced. If business communication is inappropriate or has errors, it will negatively impact a company or organization. It's time to build better business communication than before because in it you will find effective forms of communication in the business world and various forms of promotion that create great opportunities in doing business. In the economic aspect, this business communication training will make it possible to find effective business communication, so that it can become a source of income in improving the economic condition of teachers.